Decree of the Prime Minister No. 2125 of the Year 2018 on Determining the Fees and Charges of Listing the Securities and Financial Instruments in the Egyptian Exchange = قرار رئيس مجلس الوزراء رقم 2125 لسنة 2018 بشأن تحديد رسوم ومقابل قيد الأوراق المالية والأدوات المالية بالبورصة المصرية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic